Free-breathing joint bright- and black-blood cardiovascular magnetic resonance imaging for the improved visualization of ablation-related radiofrequency lesions in the left ventricle. (19th May 2022) - Bustin, A; Sridi, S; Kamakura, T; Jais, P; Stuber, M; Cochet, H
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): This research was supported by funding from the French National Research Agency under grant agreements Equipex MUSIC ANR-11-EQPX-0030, ANR-21-CE17-0034-01 and Programme d'Investissements d'Avenir ANR-10-IAHU04-LIRYC, and from the European Council under grant agreement ERC n715093. AB acknowledges a Lefoulon-Delalande Foundation fellowship administered by the Institute of France. Background: Bright-blood late gadolinium-enhanced (LGE) cardiovascular magnetic resonance (CMR) imaging can identify the sites that were ablated during prior ablation procedures (1). However, myocardial lesions visualization is often impaired by the poor contrast at the blood-scar interface on conventional bright-blood-LGE images. Purpose: To assess the performance of a novel joint bright- and black-blood LGE (SPOT) technique to visualize myocardial lesions post ablation. Methods: Three sheep (age 2 years, body weight 51.6 kg) underwent radiofrequency ablation at multiple endocardial and epicardial sites. The animals were imaged 3 months later on a 1.5-T CMR scanner using conventional post-contrast bright-blood LGE (PSIR) (1) and the proposed SPOT (2) sequences. The SPOT sequence sampled the data to simultaneously generate a black-blood image (for scar visualization) and a bright-blood image (for scar localization) in a free-breathing 2-dimensional multi-slice scan (2). A coloured representation of myocardial scarring was then generated through image fusion. A reader graded the relative scar-to-myocardium, scar-to-blood, and blood-to-myocardium contrasts and the presence of LGE on all datasets. Results: Compared with the reference bright-blood LGE images, the average scar-to-myocardium relative contrast in the SPOT images significantly increased by 102.5% to 8.1±4.4 (P<0.01). Similarly, a significant increase in scar-to-blood relative contrast (0.4±0.6 vs. 7.6±4.9, P<0.01) was observed. Owing to the nulling of both blood and normal myocardium signal, a significant decrease in blood-to-myocardium relative contrast (2.5±1.8 vs. 0.2±0.4, P<0.01) was observed with SPOT. A total of 7 and 12 lesions could be identified on conventional bright-blood LGE and proposed SPOT images, respectively (Figure). Conclusion: The higher scar-to-blood relative contrast with SPOT imaging enables the improved visualization of myocardial lesions post radiofrequency ablation. SPOT offers a promising technology for the non-invasive assessment of myocardial injuries post ablation.